Our moon : new discoveries about Earth's closest companion - Scott, Elaine, 1940- (Clarion Books, Houghton Mifflin Harcourt, 2015)
"Full of captivating, kid-friendly information, Our Moon covers everything from the newest theories on how the moon formed, to the recent, startling discovery of water on its surface and the very real possibility of future moon colonies. Illustrated with full-color photographs and packed with fun facts, this is the most complete and up-to-date book available on the moon. Includes glossary, bibliography, and index"--